Cho n ∈ Z, n > 0, với điều điều kiện nào của a thì đẳng thức sau xảy ra? $a^{-n}$ =$\frac{1}{a^{n}}$

Cho n ∈ Z, n > 0, với điều điều kiện nào của a thì đẳng thức sau xảy ra?
$a^{-n}$ =$\frac{1}{a^{n}}$

Share

1 Answer

Leave an answer

Leave an answer

Browse

Cho n ∈ Z, n > 0, với điều điều kiện nào của a thì đẳng thức sau xảy ra? $a^{-n}$ =$\frac{1}{a^{n}}$

Cho n ∈ Z, n > 0, với điều điều kiện nào của a thì đẳng thức sau xảy ra?
$a^{-n}$ =$\frac{1}{a^{n}}$

Share

1 Answer

Leave an answer

Leave an answer

Browse